Odpowiedzi

Najlepsza Odpowiedź!
2009-11-09T19:06:03+01:00
Y=2x+1
4x+y=13

y=2x+1
4x+2x+1=13 /-1

y=2x+1
6x=12 /:6

y=2*2+1
x=2

y=5
x=2


drugie

5y-x=3
x=3-y

5y-3+y=3 /+3
x=3-y

6y=6 /:6
x=3-y

y=1
x=2
2009-11-09T19:05:56+01:00
A) metodą przeciwnych współczynników:
y=2x+1
4x+y=13

-2x + y = 1 / *(-1)
4x + y = 13

2x - y = - 1
4x + y = 13
__________+
6x = 12 / :6
x=2

-2*2 + y = 1
- 4 + y = 4 +1
y=5

x=2
y=5

2009-11-09T19:12:50+01:00
A) y=2x+1
4x+y=13

{y=2x+1
{4x+2x+1=13

{y=2x+1
{6x=12

{y=2x+1
{x=2

{y=5
{x=2


b) 5y-x=3
x=3-y

{x=3-y
{5y-3+y = 3

{x=3-y
{6y=6

{x=3-y
{y=1

{x=2
{y=1


Pozdrawiam! :)